Urgensi Tawakal Dalam Ekonomi Islam - Eja Armaz Hardi (Institut Agama Islam Negeri Padngsidimpuan, 2019)
AbstractIn searching the origin of the word tawakal 38 times were repeated. 21 personal tawakal words, 11 mentioned that tawakal people are believers, 4 times the appeal for tawakal in general and 2 times the word is interpreted by delegation. Tawakal is one way to maintain good relations between the servant and Allah SWT. This vertical relationship must go hand in hand with the muamalah insaniyah relationship. In Islam, Muslims must uphold the values of trust in Allah. Because in every human activity is the result of efforts made and the intervention of Allah SWT. Then the mention of trusts 38 times. The concept of trust in the Koran is a personal activity of a servant to Allah. With many individuals trusting will form a community of faith. Meanwhile, in the context of Islamic economics, trustees will form a healthy, honest and clean market mechanism. Tawakal is also called upon to humans in general and tawakal can also be interpreted as a form of delegation of activities from one person to another.AbstrakPada penelurusan asal kata tawakal ditemui sebanyak 38 kali pengulangan. 21 kata tawakal yang bersifat personal, 11 disebutkan bahwa orang tawakal adalah orang yang beriman, 4 kali seruan untuk tawakal secara umum dan 2 kali kata tersebut dimaknai dengan delegasi. Tawakal merupakan satu dari cara untuk menjaga hubungan baik antara hamba dan Allah SWT. Hubungan vertikal ini harus beriringan dengan hubungan muamalah insaniyah. Dalam Islam, muslim harus menjunjung nilai-nilai tawakal kepada Allah. Karena dalam setiap aktifitas manusia merupakan hasil dari upaya yang dilakukan serta campur tangan Allah SWT. Kemudian penyebutan tawakal 38 kali. Konsep tawakal dalam al-Quran merupakan aktifitas personal seorang hamba kepada Allah. Dengan banyaknya individu bertawakal akan membentuk masyarakat beriman.Sedangkan dalam konteks ekonomi Islam pelaku tawakal akan membentuk mekanisme pasar yang sehat, jujur dan bersih. Tawakal juga diserukan kepada manusia secara umum dan tawakal dapat dimaknai juga sebagai bentuk delegasi kegiatan dari seseorang ke orang lain.